Epidemiology and risk factors for heat illness: 11 years of Heat Stress Monitoring Programme data from the FIVB Beach Volleyball World Tour - Racinais, S.; Alhammoud, M.; Nasir, N.; Bahr, R. (British Journal of Sports Medicine, 2021)
Objectives: To analyse 11 years of FIVB heat stress-monitoring data to determine the relative influence of the different environmental parameters in increasing the likelihood of a heat-related medical time-out (MTOheat).